2019
DOI: 10.9767/bcrec.14.3.4723.614-624
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium-doped Titania-pillared Clay for The Selective Catalytic Oxidation of Cyclohexene: Influence of Ru Loading

Abstract: A series of ruthenium-based catalysts supported on acid-activated montmorillonite (PILC) and interspersed with titanium (Ru/Ti-PILCs) were prepared with various amounts of ruthenium. Their catalytic performances in the selective oxidation of cyclohexene, using tert-butylhydroperoxide (TBHP) as oxidant were checked. The clay structure modification by acid activation and impregnation of transition metals resulted in an enhanced Lewis and Bronsted acidities. The Ru/Ti-PILCs materials were characterized using X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…This scheme takes two steps: pillarization, followed by an impregnation procedure, as described in Figure 10. Combinations such as TiO2-impregnated Fe-pillared clay (TiO2/Fe-PILC), Fe-impregnated Co-pillared clay (Fe/Co-PILC), Ru-impregnated Ti-pillared clay (Zn/Fe-PILC), and Co/Al-PILC exhibited hybrid properties for gaining either homogeneous dispersion or material stability, which are sufficiently accommodating for surface interactions for the catalytic process [147][148][149][150]. The immobilized Co 2+ and Sn 2+ have been proven as successful catalysts for dye oxidation.…”
Section: Pillarizationmentioning
confidence: 99%
See 1 more Smart Citation
“…This scheme takes two steps: pillarization, followed by an impregnation procedure, as described in Figure 10. Combinations such as TiO2-impregnated Fe-pillared clay (TiO2/Fe-PILC), Fe-impregnated Co-pillared clay (Fe/Co-PILC), Ru-impregnated Ti-pillared clay (Zn/Fe-PILC), and Co/Al-PILC exhibited hybrid properties for gaining either homogeneous dispersion or material stability, which are sufficiently accommodating for surface interactions for the catalytic process [147][148][149][150]. The immobilized Co 2+ and Sn 2+ have been proven as successful catalysts for dye oxidation.…”
Section: Pillarizationmentioning
confidence: 99%
“…The order of polymer species which determines the intercalating layers changed as the ageing temperatures changed. From varied ageing temperatures between 25 and 100 °C, it was found that different species sizes caused the irregular stacking of clay layers, and the optimum Combinations such as TiO 2 -impregnated Fe-pillared clay (TiO 2 /Fe-PILC), Fe-impregnated Co-pillared clay (Fe/Co-PILC), Ru-impregnated Ti-pillared clay (Zn/Fe-PILC), and Co/Al-PILC exhibited hybrid properties for gaining either homogeneous dispersion or material stability, which are sufficiently accommodating for surface interactions for the catalytic process [147][148][149][150]. The immobilized Co 2+ and Sn 2+ have been proven as successful catalysts for dye oxidation.…”
Section: Pillarizationmentioning
confidence: 99%
“…The partial oxidation of saturated and unsaturated hydrocarbons is a very important process in organic synthesis due to the importance of the products obtained as valuable commercial intermediates [1][2][3][4][5]. Among the unsaturated hydrocarbon compounds, cyclohexene has been the subject of great attention leading to many industrial applications [6]. It is a cheap chemical, an easily obtained raw material and can be oxidized into various oxygenated chemicals which are important intermediates for the production of drugs, pesticides, spices, surfactants, chemicals and polymers [7,8].…”
Section: Introductionmentioning
confidence: 99%